POLA KOMUNIKASI SOSIAL PADA MASYARAKAT PEMUKIMAN TANEAN LANJANG DI KABUPATEN SUMENEP MADURA - Saleh, Akhmad Muwafik (Jurnal Interaktif, 2010)
On human interaction, communication become effective medium which illustrate how they can understand and make reality. Every human result of masterpiece from interaction on their life and then itâs called with culture. Masterpiece result of culture comprehended as one of message which will send by human about how they make a meaning of live or reality look like settlement model. On that settlement model, human makes interaction and communication with each other. Recognition and understanding this pattern communication will be very benefit to see how the society producing and responding the message and do as according to culture value that are embraced.With the opinion, this research more instructed to describe how the communication pattern in society model settlement Tanean Lajang in Sumenep Regency, Madura. This research uses ethnography type to easily understand a problem from society point of view. This researchÂ  focuss on some aspect of ethnography categorize, for example: ways of speaking, Idea of the fluent speaker, speech community, Speech situation, and Speech event.This research makes conclusion that communication pattern what are embraced by Tanean Lajang society on communication pattern with based on family communication on emphasizing at the important of confirm family value aspect with limited by value of courtesy ethics. Social communication pattern on Tanean Lajang society also is colored by tendency of communications current which top down. Information in generally stream from surface or elite figure on Tanean Lajang, and then stream to ordinary citizen. Key words: Tanean Lanjang, social communication, communication pattern, ideal communicator, action and event of communication, ethnography.